Analysis optimization using numerical evaluation methods for 2D truss structure - Nurul Ashikin, Abdul Rahman (2010)
The study of the 2D truss structure can be done in laboratory by conducting laboratory test. But, usually these tests are expensive and time consuming. With the advance of computer technology and development of finite element software packages, the finite element method may provide an alternative way to analyze the 2D truss structure. In this study, the 2D truss transmission tower analyzed by using finite element ANSYS. In this structure, there are two sources of the data which are come from input parameter and output parameter graph. Output parameters are consists of maximum deflection, Maximum Stress and Maximum Strain while input parameter consists of real constant, horizontal and vertical force, Poison's ratio, and Young's Modulus. ANSYS software has advantages of factorial design and be able to generate analysis in graph without change the range and run it again. Several goodness-of-fit measures are provided for each random output parameter.